Análise da trajetória da avaliação educacional brasileira - Ristow, Simaia Zancan (2008)
This study which is inserted in the line of research in the course of Special Education Master's in Education, Federal University of Santa Maria, had the objective to seek understanding how the theories of the education evaluation assessment were historically constructed, starting from the bibliographic references from the area in a study of character bibliographic covering the period of 1930 until 2008. It is assumed that to treat the issue of educational evaluation must enter first of all, in a historical study that makes possible to understand how education assessment theories were constructed, because this is still a theme that there is a lot to be discussed and it had few changes in their characteristics related to structure. Therefore, the study about the education assessment is considered relevant concerning the paradigm of the inclusion points out the acceptance of the differences, emphasizing the students' permanence with special education needs, preferentially, in the regular teaching. Once such an issue influences directly in the inclusion process, would become, besides, the largest barriers of the inclusion. The research done in this research enabled noted that the evaluation is itself a reflection of society, economics and politics and, therefore, needs to be examined historically. It was observed that this practice has undergone many changes since its introduction in schools, even with so many speeches that emphasized the enhancement of reflection, of criticism, dialogue, assuming continues to be a procedure traditional, authoritarian and selective.